Role of soil in the regulation of human and plant pathogens: soils' contributions to people. (27th September 2021) - Samaddar, Sandipan; Karp, Daniel S.; Schmidt, Radomir; Devarajan, Naresh; McGarvey, Jeffery A.; Pires, Alda F. A.; Scow, Kate
Abstract : Soil and soil biodiversity play critical roles in Nature's Contributions to People (NCP) # 10, defined as Nature's ability to regulate direct detrimental effects on humans, and on human-important plants and animals, through the control or regulation of particular organisms considered to be harmful. We provide an overview of pathogens in soil, focusing on human and crop pathogens, and discuss general strategies, and examples, of how soils' extraordinarily diverse microbial communities regulate soil-borne pathogens. We review the ecological principles underpinning the regulation of soil pathogens, as well as relationships between pathogen suppression and soil health. Mechanisms and specific examples are presented of how soil and soil biota are involved in regulating pathogens of humans and plants. We evaluate how specific agricultural management practices can either promote or interfere with soil's ability to regulate pathogens. Finally, we conclude with how integrating soil, plant, animal and human health through a 'One Health' framework could lead to more integrated, efficient and multifunctional strategies for regulating detrimental organisms and processes. This article is part of the theme issue 'The role of soils in delivering Nature's Contributions to People'.